Resource partitioning among flower visitors and evolution of nectar concealment in multi-species communities - Rodriguez-Girones, M.A; Santamaria, L (Proceedings of the Royal Society. B, Biological sciences, 2005)
The plant community within which flower evolution takes place has largely been ignored. We develop two models for the evolution of nectar concealment when flowers are visited by legitimate pollinators and flower parasites. When there is a single plant species, no level of nectar concealment is evolutionarily stable: any population can be invaded by mutants exhibiting a higher level of nectar concealment. However, the presence of a second flower species with exposed nectar and not subject to evolution breaks the runaway process. In the presence of open flowers, depending on the fitness function there may be an evolutionarily stable level of nectar concealment, or more complex evolutionary dynamics, with nectar concealment fluctuating within a bounded range. Concealment of nectar from flower parasites can evolve even if it implies decreasing the accessibility of nectar to legitimate pollinators.